2021
DOI: 10.1002/eem2.12173
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on the Development of Functional Materials in Microbial Fuel Cells: From Fundamentals to Challenges and Outlooks

Abstract: Microbial fuel cells (MFCs), as a sustainable and promising technology to solve both environmental pollution and energy shortage, have captured tremendous attention. The conversion efficiency of chemical energy contained in organic waste or wastewater to electricity via microbial metabolism strongly depends on the performance of each functional unit, including the anode, cathode and separator/membrane used in MFCs. Therefore, significant attention has been paid toward developing advanced functional materials t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 246 publications
0
12
0
5
Order By: Relevance
“…Over the past two decades, scientists have proposed anode surface modification strategy to improve the MFC performance and have been committed to developing new anode materials that can generate higher power output. [27] Varies materials have been applied as electrodes in MFCs, mainly in consideration of their electrical conductivity, specific surface area, porosity, biocompatibility, anticorrosive property, mechanical strength, toughness, cost and so on. [28] However, the conductivity of the traditional carbonaceous electrode is relatively poor and the exoelectrogens amount adhered on the surface of the unmodified naked carbon electrode has reached the maximum limit.…”
Section: Nanomaterials For Anode Surface Modificationmentioning
confidence: 99%
“…Over the past two decades, scientists have proposed anode surface modification strategy to improve the MFC performance and have been committed to developing new anode materials that can generate higher power output. [27] Varies materials have been applied as electrodes in MFCs, mainly in consideration of their electrical conductivity, specific surface area, porosity, biocompatibility, anticorrosive property, mechanical strength, toughness, cost and so on. [28] However, the conductivity of the traditional carbonaceous electrode is relatively poor and the exoelectrogens amount adhered on the surface of the unmodified naked carbon electrode has reached the maximum limit.…”
Section: Nanomaterials For Anode Surface Modificationmentioning
confidence: 99%
“…There have been studies on microbial fuel cells (MFCs) for treating high-concentration organic dyes, which are environmental friendly and low-energy consuming. However, dyes directly mixed with microorganisms can poison them. , It is also possible that dye decolorization would be accompanied by the production of new intermediate products, which would inhibit microorganism activity and reduce the efficiency of dye removal.…”
Section: Introductionmentioning
confidence: 99%
“…However, dyes directly mixed with microorganisms can poison them. 2,3 It is also possible that dye decolorization would be accompanied by the production of new intermediate products, which would inhibit microorganism activity and reduce the efficiency of dye removal.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Therefore, the anode should be reasonably designed to have lower internal resistance and as much space as possible for the electrochemically active bacteria to attach, grow, and improve the transfer process of extracellular electrons. [17,18] Although previous studies have significantly enhanced the performance of two-dimensional (2D) carbon material anodes, [14,19,20] the shortcomings of 2D anode materials are still obvious.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotube (CNT) materials are one of the most superior nanostructured carbonaceous materials due to their outstanding electron conductivity, [25] excellent chemical stability, and high affinity with electroactive bacteria. [18,26,27] For many electrocatalytic reactions, including reactions of electron mediators produced by bacteria, the CNTs always exhibit outstanding direct electrochemical performance. [28,29] A previous study has shown that incorporating multiwalled carbon nanotubes (MWCNT) into carbon-based aerogel can greatly avoid the distortion of porous structure and form a hierarchical structure.…”
Section: Introductionmentioning
confidence: 99%